An Experimental Study of the Kinetics of the Reactions of Isopropyl, sec‐Butyl, and tert‐Butyl Radicals with Molecular Chlorine at Low Pressures (0.5–7.0 Torr) in the Temperature Range 190–480 K. Issue 12 (22nd September 2016) - Pekkanen, Timo T.; Arppe, Suula L.; Eskola, Arkke J.; Rissanen, Matti P.; Timonen, Raimo S.
ABSTRACT: In this work, we have measured the rate coefficients of the reactions of isopropyl (propan‐2‐yl), sec ‐butyl (butan‐2‐yl), and tert ‐butyl (2‐methylpropan‐2‐yl) radicals with molecular chlorine as a function of temperature (190–480 K). The experiments were done in a tubular laminar flow reactor coupled to a photoionization quadrupole mass spectrometer employing a gas‐discharge lamp for ionization. The radicals were homogeneously produced in the reactor by photolyzing suitable precursor molecules with 193‐nm pulsed exciplex laser radiation. The bimolecular rate coefficients were obtained by monitoring the radical decay signals in real time under pseudo–first‐order conditions. The rate coefficients of all three reactions showed negative temperature dependence. The bath gas used in the experiments was helium, and the rate coefficients appeared to be independent of the helium concentrations employed ([2.4–14] × 10 16 cm −3 ) for all three reactions. The rate coefficients of the reactions can be approximated in the studied temperature range by the following parameterizations: k ( i ‐ C 3 H 7 + Cl 2 ) = ( 3.70 ± 0.12 ) × 10 − 11 × ( T / 300 K ) − ( 1.98 ± 0.10 ) cm 3 s − 1 k ( s ‐ C 4 H 9 + Cl 2 ) = ( 4.90 ± 0.20 ) × 10 − 11 × ( T / 300 K ) − ( 1.92 ± 0.19 ) cm 3 s − 1 k ( t ‐ C 4 H 9 + Cl 2 ) = ( 4.46 ± 0.18 ) × 10 − 11 × ( T / 300 K ) − ( 2.97 ± 0.14 ) cm 3 s − 1 We estimate that the overall uncertainties of the measured rate coefficients are ±20%. We were able to observe 2‐chloropropane ( i ‐C3 H7 Cl) product for the i ‐C3 H7 ● + Cl2 reaction. No products were observed for the other two reactions, and the reasons for this are briefly discussed in the text.